PENGARUH MODEL PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) DAN GAYA BELAJAR TERHADAP HASIL BELAJAR GEOGRAFI DI SMA - Dewi Nur Azizah (JAMBURA GEO EDUCATION JOURNAL, 2022)
STAD is one of learning model that motivate student to support each other in understanding materials given by teacher. However, another factor which is affecting learning result is student's character. In this case, learning style as one of student's characteristic is expected affecting learning result. This research is aimed to know influence of STAD model, Learning Style, and interaction between STAD model and learning style on learning result. Hypothesis is formulated as: (1) STAD model influences learning result; (2) learning style influence learning result; (3) No influence between STAD model and learning style toward learning result. This research was designed using Quasi Experiment, with factorial design 2 x 3. Research subject was consist of two classes that X2 as control class and X4 as experiment class. Research variable was consist of: (1) student's learning result as tied variable; (2) STAD learning model as free variable; and (3) learning style as moderator variable. student's learning result was measured by test. however, learning style was measured by questionnaire. Data resulted then were analyzed using two way ANOVA with SPSS 16.00 for windows. Analysis resulted by two way anova was showing that: (1) STAD model influenced learning result; (2) learning style influenced learning result; (3) no influence found in interaction between STAD model and learning style toward learning result. Conclusions of this research were: (1) STAD model had effected learning result; (2) learning style had affected learning result; and (3) no influence found between STAD model and learning style toward learning result. It is recommended for geography teacher applying STAD model and more concerning on student's learning style because it has effect on student's learning result. For researchers it is suggested to applied in other subjects.